2011
DOI: 10.1155/2011/167156
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Profile in Multiple Sclerosis Patients

Abstract: Multiple sclerosis (MS) is a progressive demyelinating process considered as an autoimmune disease, although the causes of this pathology have not been yet fully established. Similarly to other neurodegenerations, MS is characterized by a series of biochemical changes affecting to different extent neuronal functions; great attention has been given to oxidative/nitrosative stress and to alterations in mitochondrial functions. According to previous data, MS patients show significant changes in the circulating co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
68
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 54 publications
6
68
2
1
Order By: Relevance
“…A mitochondrial dysfunction with defects of mitochondrial respiratory chain complex IV (cytochrome c oxidase) has been found in some active lesions of relapsing remitting MS patients [71]. Furthermore, a metabolomic study has revealed changes in MS patient serum levels of different metabolites and oxidants/antioxidants unbalance compared to healthy controls [72]. Moreover, increased levels of both glutamine and glutamate have been described.…”
Section: Metabolic Dysregulation In Ra and Other Autoimmune Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mitochondrial dysfunction with defects of mitochondrial respiratory chain complex IV (cytochrome c oxidase) has been found in some active lesions of relapsing remitting MS patients [71]. Furthermore, a metabolomic study has revealed changes in MS patient serum levels of different metabolites and oxidants/antioxidants unbalance compared to healthy controls [72]. Moreover, increased levels of both glutamine and glutamate have been described.…”
Section: Metabolic Dysregulation In Ra and Other Autoimmune Conditionsmentioning
confidence: 99%
“…Moreover, increased levels of both glutamine and glutamate have been described. Glutamate concentration correlates with disease severity, and glutamine is critically required for naive CD4 + T-cell differentiation toward Th1 and Th17 proinflammatory T cells [72].…”
Section: Metabolic Dysregulation In Ra and Other Autoimmune Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported significantly higher mean tNOx in RRMS compared to control groups, in acute relapse and in remission [16][17][18][19][20][21][22][23]. Most noteworthy is Tavazzi et al's study [16] of a large cohort of 113 RRMS patients in whom serum tNOx levels were significantly higher (p<0.001) in RRMS patients than in health controls. Three studies described no significant difference but were heterogeneous as to the MS disease phenotype, and none considered patients following an acute relapse [24][25][26].…”
Section: Peripheral Bloodmentioning
confidence: 99%
“…A single study [27] found the opposite: significantly lower mean tNOx in RRMS patients compared to control groups; no significant study characteristics were identified to explain this disparity. tNOx has been considered across RRMS and SPMS groups with mixed resultsone study reported significantly higher mean tNOx in RRMS than SPMS [22] whereas others reported no significant difference [16,17,23].…”
Section: Peripheral Bloodmentioning
confidence: 99%